2021
DOI: 10.3390/e23010111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Future Information and Trajectory Complexity on Kinematic Signal and Muscle Activation during Visual-Motor Tracking

Abstract: Visual-motor tracking movement is a common and essential behavior in daily life. However, the contribution of future information to visual-motor tracking performance is not well understood in current research. In this study, the visual-motor tracking performance with and without future-trajectories was compared. Meanwhile, three task demands were designed to investigate their impact. Eighteen healthy young participants were recruited and instructed to track a target on a screen by stretching/flexing their elbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Previous studies revealed the composition of EMG signals were the summation of a temporal superposition of the motor unit action potentials (MUAPs) sequence produced by the various motor units of the contracted muscles ( De Luca, 1984 ; Gazzoni et al, 2004 ; Chen and Zhou, 2016 ). As the task intensity increased, the neuromuscular control strategy adjusted and structure in motor execution increased, leading to more complicated muscle firing patterns ( Enders et al, 2015 ; Ma et al, 2017 ; Deng et al, 2021 ). As muscle power increases, more motor units are recruited, increasing the fApEn of the EMG signals ( Kamavuako et al, 2012 ; Chen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed the composition of EMG signals were the summation of a temporal superposition of the motor unit action potentials (MUAPs) sequence produced by the various motor units of the contracted muscles ( De Luca, 1984 ; Gazzoni et al, 2004 ; Chen and Zhou, 2016 ). As the task intensity increased, the neuromuscular control strategy adjusted and structure in motor execution increased, leading to more complicated muscle firing patterns ( Enders et al, 2015 ; Ma et al, 2017 ; Deng et al, 2021 ). As muscle power increases, more motor units are recruited, increasing the fApEn of the EMG signals ( Kamavuako et al, 2012 ; Chen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al proposed fuzzy approximate entropy (fApEn) based on the entropy theory by introducing the idea of a fuzzy set ( Chen et al, 2007 ). Previous studies have shown that fApEn can be used as an indicator of changes in the complexity of sEMG signals to determine the alterations in motor control during task execution ( Ao et al, 2015 ; Deng et al, 2021 ). However, the relationship between changes in muscle complexity and brain network during task execution remains unclear.…”
Section: Introductionmentioning
confidence: 99%